LANGUAGE SOCIALIZATION IN FAMILY ENVIRONMENTS THROUGH TERMS OF ADDRESS TO CHILDREN - Wira Kurniawati; Suhandano Suhandano; Bernadette Kushartanti (LITERA, 2021)
As a linguistic resource, term of address in language socialization can become a means to make children competent in language and in society. This article aims to describe the practice of language socialization that is reflected from terms of address used by parents with children in the family environment. The study took place in Sleman Regency, Yogyakarta Special Region, Indonesia. The data were obtained through questionnaires and observations. The questionnaires were distributed to parents through six schools (Play Groups, Day Care Centers, and Kindergartens) in the city center of Sleman Regency (N=145). Meanwhile, observations were made on five families living in urban Sleman. The data were analyzed by qualitative method which began with classifying the forms of address to then find out the motivation and socialization values contained in these forms of address. The results of the research indicated that, as a linguistic resource, several forms of address with various motivations were found. The forms and motivations for the preferred addresses toward children indicated that in urban family environments parents tend to rely on child-centered communication during the language socialization process. In this case, parents adapted their language usage to meet their children’s developmental levels. This is evident from the use of address in the form of proper names and kinship terms (which can be followed by proper names) that are utilized to avoid the use of second person pronouns. In addition, there is an emphasis on affection conveyed through addresses in the form of adjectival nominalization, nominal forms, terms of endearment, and various forms of appositives. The values reflected in the selection of such addresses are courtesy, affection, hope, cultural and religious identity, and position of society between locality and nationality.   Keywords: language socialization; address to children; family environment SOSIALISASI BAHASA DI LINGKUNGAN KELUARGA MELALUI KATA SAPAAN UNTUK ANAK-ANAK AbstrakSebagai salah satu sumber kebahasaan, pemakaian sapaan dalam sosialisasi bahasa dapat menjadi sarana untuk menyosialisasikan anak agar memiliki kecakapan dalam berbahasa dan bermasyarakat. Artikel ini bertujuan mendeskripsikan sosialisasi bahasa yang tecermin dari pemakaian kata sapaan oleh orang tua kepada anak di lingkungan keluarga. Penelitian berlangsung di Kabupaten Sleman, Daerah Istimewa Yogyakarta, Indonesia. Data diperoleh melalui kuesioner dan observasi. Kuesioner dibagikan kepada orang tua melalui enam sekolah (Kelompok Bermain, Tempat Penitipan Anak, dan Taman Kanak-Kanak) di Kabupaten Sleman (N = 145), sedangkan observasi dilakukan terhadap lima keluarga yang tinggal di lingkungan urban Sleman. Analisis data dilakukan dengan metode kualitatif yang diawali dengan melakukan klasifikasi bentuk-bentuk sapaan untuk kemudian mengetahui motivasi dan nilai sosialisasi yang terkandung dari bentuk-bentuk sapaan tersebut. Hasil penelitian menunjukkan bahwa sebagai sumber kebahasaan dalam sosialisasi, ditemukan beberapa bentuk sapaan dan berbagai motivasi pemakaiannya. Bentuk dan motivasi sapaan untuk anak-anak menunjukkan bahwa orang tua cenderung menggunakan komunikasi yang berpusat pada anak. Orang tua menyesuaikan penggunaan bahasa mereka untuk memenuhi tingkat perkembangan anak mereka. Hal ini terlihat dari penggunaan sapaan berupa nama diri dan istilah kekerabatan (yang dapat diikuti dengan nama diri) yang digunakan untuk menghindari penggunaan kata ganti orang kedua. Selain itu, ada penekanan pada aspek afeksi melalui sapaan berupa nominalisasi kata sifat, bentuk nominal, bentuk ungkapan kasih, dan berbagai bentuk apositif. Pemilihan jenis-jenis sapaan tersebut mengandung nilai-nilai yang secara implisit diajarkan kepada anak, yaitu kesopanan, kasih sayang, harapan, identitas budaya dan agama, serta identitas masyarakat di antara lokalitas dan nasionalitas. Kata kunci: sosialisasi bahasa, sapaan pada anak, lingkungan keluarga